A self-compacting composite concrete waterproofing agent and its preparation and use method

By using self-compressed composite concrete waterproofing agent composed of paraffin, emulsifier, polyvinyl alcohol aqueous solution, cellulose ether, modified starch and water glass, the problem of insufficient compactness in the early stage of concrete in the prior art was solved, and the crack resistance and permeability of concrete were significantly improved.

CN119038896BActive Publication Date: 2025-03-21ZHEJIANG TONGYAN GEOMETRY NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411523711.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-21
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing self-condensed concrete waterproofing agent is difficult to improve the density during the early hydration of concrete, resulting in cracks and seepage of concrete.

Method used

The self-finished composite concrete waterproofing agent consisting of paraffin, emulsifier, compacting agent, crystallization agent and water is made up of polyvinyl alcohol aqueous solution, cellulose ether and modified starch. The crystallization agent is sodium water glass or potassium water glass. This waterproofing agent significantly improves the early compactness and crack resistance of concrete by improving the conjugation and anti-isolation water secretion properties of concrete.

Benefits of technology

It significantly improves the early compactness and crack resistance of concrete, reduces the risk of cracking of concrete, and improves its permeability and service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a self-compacting composite concrete waterproofing agent and its preparation and use method, the waterproofing agent is composed of 15-20 parts of paraffin, 2-3 parts of emulsifier, 15-25 parts of densifier, 10-15 parts of crystallizer, and 40-55 parts of water, and the densifier is composited by 15% polyvinyl alcohol aqueous solution, cellulose ether, and modified starch. The preparation method of the waterproofing agent is: paraffin is added to water in proportion and heated to completely melt; then an emulsifier is added in proportion to make the paraffin begin to emulsify, and stirred for 10 minutes-20 minutes; a densifier is added in proportion, heating is stopped, and stirring is continued until the system returns to room temperature; finally, a crystallizer is added in proportion and stirred until the system is uniform. The preparation method provided by the present invention is simple to operate, and the prepared waterproofing agent system is stable, and mixing in concrete can significantly increase the compactness of concrete, and the cracks generated in the later stage of concrete have the function of crystallization self-repairing, and paraffin can enhance the waterproof performance of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete admixtures, and in particular to a self-compacting composite concrete waterproofing agent and a preparation and use method thereof. Background Art

[0002] Concrete is one of the most widely used materials in today's construction projects. Concrete is made of cement as a binder, sand and stone as aggregates, water and appropriate admixtures and additives. Insufficient concrete density will directly affect its strength, durability and waterproof performance, leading to cracks and water seepage in the concrete structure.

[0003] In the prior art, the use of self-compacting concrete waterproofing agents can form a dense layer at a microscopic level in the concrete structure, playing an important role in solving problems such as insufficient concrete density and cracking.

[0004] For example, Chinese patent CN102718553B provides a concrete waterproofing and compacting agent and its preparation method, which is composed of the following raw materials in weight ratio, including 10%-13% potassium hydroxide; 0.5-1% volcanic ash; 0.5-1% potassium oleate; 10%-12% sulfur; 0.5%-1% propylene glycol; 3%-5% aminotriethanol; 0.5-1% citric acid; 0.5%-1.5% ferric oxide; 0.5%-1% sodium fluorosilicate; and the rest is water. Its mechanism is that the concrete waterproofing and compacting agent can react chemically with silicon, calcium, sodium, magnesium, etc. contained in cement, and the generated chemical crystals and colloids can effectively organize the penetration of water molecules, significantly improve the strength, and can make the concrete particles bond more tightly while reducing shrinkage by 30%, effectively controlling cracking.

[0005] For example, Chinese patent CN111233370B provides a self-compacting waterproofing agent for concrete structure and its preparation method and application, which includes the following components by mass: 16-19 parts of alkyl silicate, 15-18 parts of fluorosilicate, 3-7 parts of dispersant, 2-4 parts of aluminum liquid, 4-7 parts of water reducer and 2-5 parts of slump retainer. Its mechanism is that the silanol group in the alkyl silicate can react with the silanol group in the concrete silicate material to dehydrate and crosslink, thereby realizing the "reverse capillary effect", and at the same time has the functions of micro-expansion, increasing the density of concrete, and reducing concrete shrinkage cracks. There is no strict restriction on the alkyl silicate, for example, it can be selected from at least one of sodium methyl silicate, potassium methyl silicate, sodium ethyl silicate and potassium ethyl silicate, preferably sodium methyl silicate; at the same time, the use of a dispersant can disperse the cement particles, release the water contained in the cement agglomerate, improve the workability of the concrete, and increase the density and strength of the concrete. The dispersant is not strictly limited, and for example, it can be selected from at least one of sodium pyrophosphate, sodium hexametaphosphate and sodium gluconate, preferably sodium pyrophosphate.

[0006] The shortcomings of the above patents are that the self-compacting concrete waterproofing agents reported so far mostly use functional components to react with metal ions produced during the concrete water hardening process to form crystals to block the concrete pores and thus improve the concrete density. However, the hydration process of concrete is a slow process. Generally, it takes about one month for concrete to go from initial solidification and curing to concrete strength reaching the design requirements. The formation of hydration crystals inside the concrete is also a slow process, so this type of method cannot meet the requirements for improving the early density of concrete. In order to improve the early density of concrete, a more effective method should be to improve the cohesiveness and anti-segregation and water seepage performance during the concrete mixing process, thereby improving the workability of concrete to significantly improve the early density of concrete and prevent early cracking of concrete. Summary of the invention

[0007] The purpose of the present invention is to solve the above-mentioned problem of cracks and water seepage caused by insufficient density of concrete, and to provide a self-compacting composite concrete waterproofing agent and a preparation and use method thereof.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] On the one hand, the present invention provides a self-compacting composite concrete waterproofing agent, which consists of 15-20 parts by weight of paraffin, 2-3 parts by weight of emulsifier, 15-25 parts by weight of densifier, 10-15 parts by weight of crystallizer, and 40-55 parts by weight of water. The densifier is composited by 15% by weight of polyvinyl alcohol aqueous solution, cellulose ether, and modified starch, wherein the weight ratio of 15% polyvinyl alcohol aqueous solution, cellulose ether, and modified starch is 15-18:2-3:2-4.

[0010] Furthermore, the emulsifier is a composite of triethanolamine, isomeric tridecanol polyoxyethylene ether, lauryl alcohol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether.

[0011] Furthermore, the cellulose ether is one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose, and the modified starch is one of phosphate starch, cationic starch, and oxidized starch.

[0012] Furthermore, the crystallization agent is sodium water glass or potassium water glass.

[0013] On the other hand, the present invention provides a method for preparing a self-compacting composite concrete waterproofing agent, comprising the following steps: adding paraffin wax to water in proportion according to parts by weight, heating to 70°C-75°C until completely melted; then adding an emulsifier in proportion to emulsify the paraffin, and stirring for 10 minutes-20 minutes; then adding a densifier in proportion, stopping heating, and continuing to stir until the system returns to room temperature; finally adding a crystallizer in proportion, stirring for 10 minutes-20 minutes until the system is uniform, to obtain a finished self-compacting composite concrete waterproofing agent.

[0014] The present invention also provides a method for using a self-compacting composite concrete waterproofing agent, comprising the following steps: taking the self-compacting composite concrete waterproofing agent, adding 0.7% to 1.2% of the weight of cement in the concrete to the self-compacting composite concrete waterproofing agent during concrete mixing, and stirring evenly for use.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1. The compacting agent in the self-compacting composite concrete waterproofing agent is composed of polyvinyl alcohol aqueous solution, cellulose ether and modified starch. Polyvinyl alcohol aqueous solution has the characteristics of high viscosity; cellulose ether has excellent water retention and thickening effects; modified starch has excellent anti-sinking and anti-slip properties. The composite use of polyvinyl alcohol aqueous solution with suitable cellulose ether and modified starch can maximize the performance advantages and synergistic effects of each, thereby significantly improving the cohesiveness of concrete, improving the segregation and bleeding of concrete, which helps to improve the workability of concrete, make concrete more uniform and stable during mixing, transportation and pouring, make the pore structure of concrete more compact, and reduce the number and diameter of capillaries inside concrete. This mechanism of action can significantly improve the impermeability of concrete; at the same time, it makes the moisture distribution in concrete more uniform. This uniform moisture distribution helps to reduce shrinkage cracks caused by uneven moisture evaporation during the drying process of concrete, thereby significantly improving the crack resistance of concrete.

[0017] 2. The crystallizing agent in the self-compacting composite concrete waterproofing agent is sodium water glass or potassium water glass. Water glass contains highly active silica sol. When microcracks appear in the concrete and cause leakage, the highly active silica sol in the water glass can react with the calcium ions in the concrete to form calcium silicate crystals to repair these cracks.

[0018] 3. The paraffin in the self-compacting composite concrete waterproofing agent can enhance the waterproof performance of concrete. DETAILED DESCRIPTION

[0019] The present invention is further explained below by examples, but the examples are only used to illustrate the present invention, rather than to limit the present invention. Other examples obtained by modifying the present example by those skilled in the art without creative contribution all belong to the scope of protection of the present invention. Example 1

[0020] A self-compacting composite concrete waterproofing agent comprises the following raw materials in parts by weight: 17 parts of paraffin, 1.7 parts of isomeric tridecanol polyoxyethylene ether, 0.8 parts of lauryl alcohol polyoxyethylene ether, 16 parts of 15% polyvinyl alcohol aqueous solution, 2.5 parts of carboxymethyl cellulose, 3 parts of phosphate starch, 12 parts of potassium water glass, and 47 parts of water.

[0021] The preparation method of the 15% polyvinyl alcohol aqueous solution is as follows: polyvinyl alcohol is added into water, soaked and swelled at room temperature for 48 hours, and then heated and stirred at 60-90° C. to dissolve, thereby obtaining a finished product.

[0022] The preparation method of the self-compacting composite concrete waterproofing agent is as follows: 17 parts of paraffin wax is added to 47 parts of water, and the mixture is heated to 70-75°C until it is completely melted; then 1.7 parts of isomeric tridecanol polyoxyethylene ether and 0.8 parts of lauryl alcohol polyoxyethylene ether are dripped in sequence, and the paraffin wax begins to emulsify, and the mixture is stirred for 15 minutes; then 16 parts of a 15% polyvinyl alcohol aqueous solution, 2.5 parts of carboxymethyl cellulose, and 3 parts of phosphate starch are added in sequence, heating is stopped, and stirring is continued until the system returns to room temperature; finally 12 parts of potassium water glass are added, and the mixture is stirred for 15 minutes until the system is uniform. Due to heating during the production process, the system loses water, and the lost water needs to be replenished in the end.

[0023] The method of using the self-compacting composite concrete waterproofing agent is as follows: the dosage is 1% of the cement dosage in the concrete. Example 2

[0024] A self-compacting composite concrete waterproofing agent comprises the following raw materials in parts by weight: 19 parts of paraffin, 2 parts of triethanolamine, 0.7 parts of fatty alcohol polyoxyethylene ether, 15 parts of 15% polyvinyl alcohol aqueous solution, 3 parts of hydroxypropyl methylcellulose, 3.5 parts of oxidized starch, 13 parts of potassium water glass, and 43.8 parts of water.

[0025] The preparation method of the 15% polyvinyl alcohol aqueous solution is as follows: polyvinyl alcohol is added into water, soaked and swelled at room temperature for 48 hours, and then heated and stirred at 60-90° C. to dissolve, thereby obtaining a finished product.

[0026] The preparation method of the self-compacting composite concrete waterproofing agent is as follows: 19 parts of paraffin wax is added to 43.8 parts of water, and the mixture is heated to 70-75° C. until the mixture is completely melted; then 2 parts of triethanolamine and 0.7 parts of fatty alcohol polyoxyethylene ether are dripped in sequence, the paraffin wax begins to emulsify, and the mixture is stirred for 15 minutes; then 15 parts of a 15% polyvinyl alcohol aqueous solution, 3 parts of hydroxypropyl methylcellulose, and 3.5 parts of oxidized starch are added in sequence, the heating is stopped, and the mixture is stirred until the mixture returns to room temperature; finally 13 parts of potassium water glass are added, and the mixture is stirred for 15 minutes until the mixture is uniform; the mixture loses water due to heating during the production process, and the lost water needs to be replenished in the end.

[0027] The method of using the self-compacting composite concrete waterproofing agent is as follows: the dosage is 0.8% of the cement dosage in the concrete. Example 3

[0028] A self-compacting composite concrete waterproofing agent comprises the following raw materials in parts by weight: 15 parts of paraffin, 0.7 parts of isomeric tridecanol polyoxyethylene ether, 0.8 parts of lauryl alcohol polyoxyethylene ether, 0.7 parts of fatty alcohol polyoxyethylene ether, 15 parts of 15% polyvinyl alcohol aqueous solution, 2 parts of hydroxyethyl cellulose, 2.4 parts of cationic starch, 10 parts of sodium water glass, and 53.4 parts of water.

[0029] The preparation method of the 15% polyvinyl alcohol aqueous solution is as follows: polyvinyl alcohol is added into water, soaked and swelled at room temperature for 48 hours, and then heated and stirred at 60-90° C. to dissolve, thereby obtaining a finished product.

[0030] The preparation method of the self-compacting composite concrete waterproofing agent is as follows: 15 parts of paraffin wax are added to 53.4 parts of water, and the mixture is heated to 70-75°C until it is completely melted; then 0.7 parts of isomeric tridecanol polyoxyethylene ether, 0.8 parts of lauryl alcohol polyoxyethylene ether, and 0.7 parts of fatty alcohol polyoxyethylene ether are sequentially added dropwise, and the paraffin wax begins to emulsify and is stirred for 15 minutes; then 15 parts of a 15% polyvinyl alcohol aqueous solution, 2 parts of hydroxyethyl cellulose, and 2.4 parts of cationic starch are sequentially added, heating is stopped, and stirring is continued until the system returns to room temperature; finally 10 parts of sodium water glass are added, and the mixture is stirred for 15 minutes until the system is uniform. Due to heating during the production process, the system loses water, and the lost water must be replenished at the end.

[0031] The method of using the self-compacting composite concrete waterproofing agent is as follows: the dosage is 1.2% of the cement dosage in the concrete.

[0032] In order to more intuitively demonstrate the synergistic effect of each component in the compacting agent of the present invention, a further explanation is given below through comparative examples. The compacting agent in the comparative example is a composite of two of 15% polyvinyl alcohol aqueous solution, cellulose ether, and modified starch.

[0033] Comparative Example 1:

[0034] The difference between Comparative Example 1 and Example 1 is that the "3 parts of phosphate starch" in Example 1 is removed, and the "47 parts of water" in Example 1 is changed to "50 parts of water".

[0035] Comparative Example 2:

[0036] The difference between Comparative Example 2 and Example 2 is that "3 parts of hydroxypropyl methylcellulose" in Example 2 is removed, and "43.8 parts of water" in Example 2 is changed to "46.8 parts of water".

[0037] Comparative Example 3:

[0038] The difference between Comparative Example 3 and Example 3 is that the "15 parts of 15% polyvinyl alcohol aqueous solution" in Example 3 is removed, and the "53.4 parts of water" in Example 3 is changed to "68.4 parts of water".

[0039] The early crack resistance test of concrete with waterproofing agent was carried out on Examples 1 to 3 and Comparative Examples 1 to 3 (total crack area per unit area, mm 2 / m 2 ), the detection method is as follows:

[0040] Early crack resistance test (total crack area per unit area, mm 2 / m 2 ): Tested in accordance with the test method in standard GB / T 50082-2009.

[0041] The test results are shown in Table 1

[0042] Test items <![CDATA[Early anti-cracking experiment (total cracking area per unit area, mm 2 / m 2 )]]> Reduction rate of total crack area per unit area compared with blank concrete (%) Blank concrete 27 — Example 1 4 85.2% Example 2 3 88.9% Example 3 6 77.8% Comparative Example 1 12 55.6% Comparative Example 2 10 59.3% Comparative Example 3 15 44.5%

[0043] Table 1

[0044] From the test results in Table 1, it can be seen that compared with the blank concrete, the total crack area per unit area of ​​Examples 1 to 3 and Comparative Examples 1 to 3 is significantly reduced, but the reduction rate of the total crack area per unit area of ​​Examples 1 to 3 is more significant than that of Comparative Examples 1 to 3, indicating that the concrete prepared by Examples 1 to 3 is more compact. On the other hand, it also shows that the composite use of polyvinyl alcohol aqueous solution and appropriate cellulose ether and modified starch can maximize the performance advantages and synergistic effects of each component, thereby greatly reducing the risk of early cracking of concrete.

[0045] To further demonstrate the waterproof performance of Examples 1 to 3, the 28d / 56d anti-seepage pressure (MPa) of the concrete mixed with the waterproofing agent was tested, and the testing method was as follows:

[0046] 28d / 56d impermeability pressure (MPa): tested in accordance with the test method in standard GB 18445-2012.

[0047] The test results are shown in Table 2

[0048] Test items 28d anti-seepage pressure (MPa) 56d anti-seepage pressure (MP) Base concrete 0.3 0.4 Example 1 0.9 0.9 Example 2 0.9 1.1 Example 3 0.8 0.9

[0049] Table 2

[0050] It can be seen from the test results in Table 2 that, compared with the benchmark concrete, the 28d / 56d impermeability pressure (MPa) of Examples 1 to 3 are significantly improved, indicating that the self-waterproofing ability of the concrete during use is significantly improved, extending its service life.

[0051] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A self-compacting composite concrete waterproofing agent, characterized in that: The self-compacting composite concrete waterproofing agent is composed of 15-20 parts by weight of paraffin, 2-3 parts by weight of emulsifier, 15-25 parts by weight of compacting agent, 10-15 parts by weight of crystallizing agent, and 40-55 parts by weight of water. The compacting agent is composited by 15% polyvinyl alcohol aqueous solution, cellulose ether, and modified starch, wherein the weight ratio of 15% polyvinyl alcohol aqueous solution, cellulose ether, and modified starch is 15-18:2-3:2-4; The cellulose ether is one of carboxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose, and the modified starch is one of phosphate starch, cationic starch and oxidized starch; The crystallizing agent is sodium water glass or potassium water glass.

2. The self-compacting composite concrete waterproofing agent according to claim 1, characterized in that: The emulsifier is a composite of triethanolamine, isomeric tridecanol polyoxyethylene ether, lauryl alcohol polyoxyethylene ether and fatty alcohol polyoxyethylene ether.

3. A method for preparing the self-compacting composite concrete waterproofing agent according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: adding paraffin wax into water in proportion, heating to 70-75°C until completely melted; then adding an emulsifier in proportion to emulsify the paraffin wax, and stirring for 10-20 minutes; then adding a compacting agent in proportion, stopping heating, and continuing stirring until the system returns to room temperature; finally adding a crystallizing agent in proportion, stirring for 10-20 minutes until the system is uniform, and obtaining a finished self-compacting composite concrete waterproofing agent.

4. A method for using the self-compacting composite concrete waterproofing agent according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: taking a self-compacting composite concrete waterproofing agent, adding 0.7% to 1.2% of the weight of cement in the concrete into the self-compacting composite concrete waterproofing agent during concrete mixing, and stirring evenly for use.

Citation Information

Patent Citations

  • Waterproof concrete compacting agent and preparation method thereof

    CN102718553B

  • A self-compacting waterproofing agent for concrete structures, its preparation method and application

    CN111233370B

  • Permeable crystalline waterproof coating

    CN101891432A

  • Efficient waterproof anti-seeping agent

    CN106007506A